Evaluating spatial and temporal effects of planned special events on travel time performance measures. (July 2020) - Pulugurtha, Srinivas S.; Duddu, Venkata R.; Venigalla, Mohan
Abstract: The effect of a planned special event on travel time performance measures varies spatially and temporally based on the type of the planned special event. Evaluating and assessing the effect helps practitioners proactively plan and improve traffic operations within its vicinity during the future planned special event. The objective of this paper, therefore, is to adopt a systemic evaluation method and examine the effect of a planned special event on travel time performance measures, over time and space, from the location of the planned special event. Raw travel time data obtained from a private data source was used to assess the spatial and temporal effects of two planned special events on travel time performance measures. Data were captured for each major road link within 3-miles of each planned special event location. Statistical analyses such as the t -test and Cohen's D were conducted to assess the difference in travel time performance measures during the day of the planned special event compared to the normal day. A statistically significant increase in travel times and travel time variations was observed on the day of the planned special event when compared to the normal day. However, the effect of the increase in travel times was observed to be small, whereas, the effect of the increase in the travel time variation was observed to be higher. Buffer time index (BTI) and planning time index (PTI) were observed to be significantly higher during the NASCAR race and for longer periods compared to the NFL game. Highlights: Increase in travel times and their standard deviations on the day of the planned special events are observed compared to a normal day. Increase in travel times was observed to be small while the effect of the increase in the standard deviation was observed to be higher. BTI and PTI were observed to be significantly higher during the NASCAR race and for longer time periods compared to the NFL game. Effect over space depends on the type of planned special event.